Fishing in a congested sea: What do marine protected areas imply for the future of the Maltese artisanal fleet?. (October 2017) - Said, Alicia; MacMillan, Douglas; Schembri, Michael; Tzanopoulos, Joseph
Abstract: Inshore artisanal fishing in Malta is under intense spatial competition as the coastal zone is fragmented by multiple uses and designations including maritime transport, infrastructure, industrial fisheries, aquaculture, tourism and recreation. This research, adopting a grounded visualization methodology, explains how the artisanal fishing sector has undergone and been affected by 'spatial squeezing'. Our results show that artisanal fishermen have been forced to give up fishing grounds or co-exist with other uses to the point where the ability to fish is becoming increasingly challenging. These difficulties might escalate with the advent of the marine protected areas (MPAs) which encompass nearly half of the inshore fishing zones. Since there does not seem to be effective MPA consultation mechanisms that elicit the real social, cultural and economic value of artisanal fishing grounds, fishermen feel threatened, alienated and disempowered. This study urges for a more holistic approach to spatial marine planning and accentuates the need of realizing the dependency of the artisanal sector on the inshore zones in the implementation of conservation measures, such that the prolonged existence of the coastal fishing communities is not jeopardized. Highlights: This research explores the socio-spatial challenges faced by inshore fishermen in Malta. Novel geographic approaches combine qualitative, quantitative and visual methods within a grounded visualization framework. The coastal zone is mosaicked by various uses which pose spatial and resource competition to fishers. The designated marine protected areas encompass 42% of the traditional inshore fishing grounds. Marine spatial planning necessitates effective participatory governance approaches.